Detection of linezolid resistance cfr gene among MRSA isolates - Muneeba Wali; Mir Sadiq Shah; Tayyab Ur Rehman; Hammad Wali; Masroor Hussain; Laiq Zaman; Fahim Ullah Khan; Autif Hussain Mangi (Elsevier, 2022)
Background: Linezolid (Oxazolidinones) is commonly used against a variety of Gram-positive infections, especially methicillin-resistant Staphylococcus aureus (MRSA). The emerging resistance to linezolid curtail the treatment of infections caused by MRSA and other Gram-positive bacteria. Presence of cfr gene plays a crucial role in Linezolid resistance. Objective: Present study was aimed to detect cfr gene among clinical MRSA isolates. Materials and methods: The suspected Staphylococcus aureus isolates were processed through Kirby Bauer disc diffusion methods for the confirmation of MRSA strains. Phenotypic Linezolid resistance was determined through broth micro-dilution method. The plasmid and DNA of Linezolid resistant isolates were subjected to molecular characterization for the presence of cfr gene. Results: Among 100 Staphylococcus aureus isolates, 85 of them were confirmed as MRSA isolates. Categorically, 65% MRSA isolates were sensitive to linezolid with MIC lower than 8 µg/ml, whereas, 35% of them were resistant to linezolid having MIC greater than 8 µg/ml. MIC level of 128 µg/ml was observed among 3.5% of the resistant isolates. Similarly, MIC level of 64 µg/ml, 32 µg/ml, 16 µg/ml and 8 µg/ml were noted for 3.5%, 4.7%, 8.2% and 15.3% isolates respectively. Linezolid resistance cfr gene was detected only in 9.4% of the resistant isolates. Conclusion: Multi drug resistance among MRSA isolates is keenly attributed to the presence of cfr gene as evident in the present study, and horizontal dissemination of cfr gene among MRSA strains is accredited to cfr-carrying transposons and plasmids.